The Effect of Allied Health and Nursing Staff’s Online Covid-19 Related Information-Seeking Behaviors on Preventive Behaviors against Covid-19 - Kahouei, Mehdi; Momeni, Marjan; Pahlevanynejad, Shahrbanoo; Rahaei, Fatemeh; Yaghoobi, Samira Sadat; Soltani-Kermanshahi, Mojtaba (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To evaluate allied health and nursing staff’s online COVID-19 related information-seeking behavior to prevent COVID-19 infection. Methodology: This study was cross-sectional research performed from February to May 2020 that surveyed allied health and nursing staff working in healthcare settings, whether full or part-time, of Semnan University of Medical Sciences, Iran. Two valid questionnaires, such as preventive behaviors and online COVID-19 related information-seeking behaviors, were used. Multiple logistic models were used to explain the correlation between one dependent binary variable and other variables. Results: 291(94.8%) had good preventive behaviors. 239 (77.9%) of the participants, after getting online health information from the Internet, very often search the obtained data in other books and journals; 240 (78.2%) very often compare the received data with information on other websites; 252 (82.1%) very often consulted with physicians about the obtained information. There was a relationship between online COVID-19 related information-seeking behaviors (Beta = 0.04, 95% CI: 1.02-1.06 and P<0.001) and preventive behaviors. Conclusion: Health-care workers use various information-seeking strategies to decrease the chance of finding inaccurate data and misjudging the correct data. This study shows that healthcare workers’ behavior to see credible information related to COVID-19 significantly affects their preventive behaviors. Keywords: Information seeking behavior, Preventive behaviors, COVID-19, Internet, Allied health, nursing staff.